Vaccination willingness among undergraduates: role of conspiracy mentality and belief in Covid-19 vaccine conspiracies - Mubeen Akhtar; Fayyaz Ahmad Faize; Shamyle Rizwan Khan; Safa Waris (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate willingness to vaccination, conspiracy mentality, and belief in vaccine conspiracies among undergraduate students as well as the level of adherence to non-pharmaceutical interventions during the coronavirus disease-2019 pandemic. Method: The cross-sectional study was conducted from January to June, 2021, and comprised undergraduate students from Islamabad and Rawalpindi, Pakistan. Data was gathered using the General Conspiracy Mentality Scale and the Belief in Vaccine Conspiracies Scale. Willingness for vaccination and degree of adherence to non-pharmaceutical interventions was measured on a 5-point rating scale. Data was analysed using SPSS 26. Results: Of the 300 subjects, ?? were males and ?? were females. The overall mean age of the sample was ??. About one-third of the sample believed in vaccine conspiracies, while only one quarter showed disagreement. High scores on conspiracy mentality (p<0.020) and belief in vaccine conspiracies (p<0.006) were associated with little adherence to behavioural recommendations for coronavirus disease-2019. High scorers on conspiracy mentality (p<0.006) and belief in vaccine conspiracies (p<0.004) had less willingness for vaccination. There was no significant difference in the conspiracy mentality and belief in vaccine conspiracies with reference to gender (p>0.05). Conclusion: Medical practitioners and healthcare organisations need to understand the connection between belief in vaccine conspiracies and related vaccine resistance and noncompliance with behavioural recommendations in the face of a pandemic. Key Words: Vaccination, Intentions, Vaccine conspiracies, Adherence to NPI, Undergraduates.